The Influence of Salary Satisfaction, Workload, and Career Development on Turnover Intention Mediated by Burnout (An Empirical Study on Employees of PT Zando Anugerah Nusantara Digital) - Achmad Fauzy Rifai (PT. Publikasiku Academic Solution, 2025)
This study aims to analyze the effect of salary satisfaction, workload, and career development on turnover intention with burnout as a mediating variable among employees of PT Zando Anugerah Nusantara Digital. The background of this research is the high level of turnover intention, which has the potential to disrupt operational stability and organizational performance. The research employed a quantitative method with the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. The population consisted of all employees of PT Zando Anugerah Nusantara Digital, with a sample of 112 respondents determined using Slovin’s formula. Data were collected through a questionnaire and processed using SmartPLS software. The measurement model (outer model) was assessed through convergent validity, discriminant validity, and composite reliability, while the structural model (inner model) was evaluated using path coefficient analysis, t-statistic, and p-value. The results showed that salary satisfaction and workload had a significant effect on burnout, while career development had no significant effect on burnout. Burnout was found to have a significant effect on turnover intention. Furthermore, salary satisfaction and workload significantly affected turnover intention through burnout, whereas career development had no significant effect on turnover intention through burnout. The conclusion of this study is that burnout plays an important role as a mediator in the relationship between salary satisfaction and workload toward turnover intention. Therefore, companies need to enhance salary satisfaction and effectively manage workload to reduce burnout levels and minimize employees’ intention to leave the organization.